(untitled) (Studia Prawnicze / The Legal Studies, 2018)
In contemporary contract and consumer law, obligations to inform are an example of instruments (protective ones) which imposes on business entities a duty to make a statement of knowledge (a representation), the content of which is determined by regulations and the purpose of which is to aid the consumer in taking a well-informed, rational decision. Appropriate regulations referring to liability for failing to carry out this obligation to inform aim to maintain optimal trust between the contracting parties and, as a result, lead to a balance in the parties’ position, at the same time upholding the principle of the freedom of contract. In accordance with the fundamental assumption in European consumer law, one’s liability towards a consumer should meet the criteria of both efficiency and proportionality, which means that one should not strictly consider such liability purely formally, i.e., as maintaining an economic balance between the parties. The sanction the company shall incur is to serve the actual satisfaction of the interests of the consumer, and not only to make a profit. Additionally, the sanctions for neglecting the obligation to inform are expected to encourage companies to comply with them. Neglecting this obligation to inform in the pre-contractual phase may take the form of not providing information which is required and explicitly defined by law or providing incomplete information. A large amount of detail in determining a business’s responsibility is presumedto guarantee the consumer knowledge of his/her rights and to enable him/her to evaluate the risks resulting from entering into a particular transaction. One must not, however, ignore the fact that providing excessive, thus illegible, information must be treated equally to non-disclosure of such information, which may result in infringement of the aforementioned regulations. Neglecting the obligation to inform may also arise in such a case where the consumer is not provided with a particular piece of information, despite the lack of a definite legal basis in this regard – such as a detailed regulation contained in an act – but such a duty would result from a general loyalty duty between the contracting parties. In the beginning, it should be noted that the liability for an infringement of the pre-contractual obligation to inform is characterised by system heterogeneity. In particular, it refers to the distinct consumer protection regime. It is very often the case that depending on the contractor’s status (professional or nonprofessional) the legal consequences of failing to inform or improperly informing are framed in different ways. One must bear in mind the difference between solely the failure to inform or to improperly carry out the pre-contractual obligation to inform (pursued within pre-contractual liability, fundamentally according to an ex delicto regime) and the consequences arising from the content of the delivered information, i.e., the guarantee of definite elements in the legal relationship of an obligatory nature (assigned to the classic liability in an ex contractu regime). The subject of civil liability for the infringement of duties to inform can be analysed from two perspectives: firstly, from an economic point of view, i.e., whether for the aggrieved party and for the market at large it would be more favourable for the infringement of the duty to inform to be pursued within an ex contractu or ex delicto regime, and secondly, from the perspective of the theory of law, whether for the system of contract law it would be better for this liability to be pursued within an ex contractu or ex delicto regime. In response to the second question, the position of academics is that the liability for the violation of trust due to failing to properly inform the consumer should be pursued in an ex delicto system in order to maintain the internal cohesion of contract law.